2016
DOI: 10.1017/s1751731115001883
|View full text |Cite
|
Sign up to set email alerts
|

Factor analysis for genetic evaluation of linear type traits in dual-purpose autochthonous breeds

Abstract: Factor analysis was applied to individual type traits (TT) scored in primiparous cows belonging to two dual purpose Italian breeds, Rendena (REN; 20 individual type traits evaluated on 11 399 first parity cows), and Aosta Red Pied (ARP; 22 individual type traits evaluated on 36 168 primiparous cows). Six common latent factors (F1 to F6; eigenvalues ⩾ 1) which explained 63% (REN) and 58% (ARP) of the total variance were obtained. F1 included TT mainly related to muscularity, and F2 to body size. The F3 and F4 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 24 publications
6
16
0
1
Order By: Relevance
“…The total variance for PCA was higher than 49.74% (2 components) reported by Guiterrez and Goyache (2002) and lower than 65.77% (7 components) reported by Roughsedge et al (2000) for 10 and 23 type traits, respectively. For FA, Mazza et al (2016a) selected 6 factors with eigenvalues greater than 1 for both Rendena and Aosta Red Pied cattle accounting for 63% (20 type traits) and 58% (22 type traits) of the total variability in the 2 dual-purpose breed, whereas Mantovani et al (2005) used 23 type traits and selected 7 factors with eigenvalues greater than 1 accounting for 63% total variability. The total variations in the aforementioned studies were higher than the total variability recorded in our study.…”
Section: Pca and Famentioning
confidence: 99%
See 2 more Smart Citations
“…The total variance for PCA was higher than 49.74% (2 components) reported by Guiterrez and Goyache (2002) and lower than 65.77% (7 components) reported by Roughsedge et al (2000) for 10 and 23 type traits, respectively. For FA, Mazza et al (2016a) selected 6 factors with eigenvalues greater than 1 for both Rendena and Aosta Red Pied cattle accounting for 63% (20 type traits) and 58% (22 type traits) of the total variability in the 2 dual-purpose breed, whereas Mantovani et al (2005) used 23 type traits and selected 7 factors with eigenvalues greater than 1 accounting for 63% total variability. The total variations in the aforementioned studies were higher than the total variability recorded in our study.…”
Section: Pca and Famentioning
confidence: 99%
“…The aggregation of these traits in selection index may be hampered by collinearity between some traits due to a coherent (co)variance matrix (Macciotta et al, 2012). The PCA and FA are 2 statistical approaches that can be used to avoid analyzing large numbers of highly correlated traits and explore the relationship between traits with minimal loss of information (Schneider and Fikse, 2007;Mazza et al, 2016a). In this way, correlated traits could be loaded in the same PC or latent factor with each including traits with common biological or physiological characters, or both (Ali et al, 1998).…”
Section: Pca and Famentioning
confidence: 99%
See 1 more Smart Citation
“…The main derived factors typically include correlated traits and may assume a biological meaning (Ali et al, 1998). Factor analysis has been widely studied as a tool for genetic evaluation of type traits in some Italian cattle, both in specialized beef breeds (Chianina, Marchigiana, and Romagnola;Forabosco et al, 2005), and in local dual-purpose cattle as Rendena and Aosta Red Pied Mazza et al, 2016). Dwelling on the milk yield, current genetic evaluation largely uses single test day (TD) records to enable earlier selection decisions (Bilal and Khan, 2009) and to improve selection accuracy respect to the traditional 305-d lactation yields (Schaeffer et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…There are some studies in this field; Kern et al (2014) found two factors for Brazilian Holstein cattle, Chu and Shi (2002) reported four factors for Holstein cows, while Mazza et al (2016) found six factors for Rendena and Aosta Red Pied dualpurpose Italian breeds.…”
Section: Discussionmentioning
confidence: 99%